Data on university library and information science programmes in Spain: 2010 - De-la-Moneda-Corrochano, Mercedes (Anuario ThinkEPI, 2012)
A picture is presented of the state of university studies in library and information science in Spain. Descriptive and statistical data on existing institutions, degree levels, student enrolment and faculty are provided.